Neurological symptoms and axonal damage in COVID-19 survivors: are there sequelae? - Bozzetti, Silvia; Ferrari, Sergio; Zanzoni, Serena; Alberti, Daniela; Braggio, Michele; Carta, Sara; Piraino, Francesco; Gabbiani, Daniele; Girelli, Domenico; Nocini, Riccardo; Monaco, Salvatore; Crisafulli, Ernesto; et al. (Immunologic research, 2021)
The persistence of neurological symptoms after SARS-CoV-2 infection, as well as the presence of late axonal damage, is still unknown. We performed extensive systemic and neurological follow-up evaluations in 107 out of 193 consecutive patients admitted to the COVID-19 medical unit, University Hospital of Verona, Italy between March and June 2020. We analysed serum neurofilament light chain (NfL) levels in all cases including a subgroup ( n = 29) of patients with available onset samples. Comparisons between clinical and biomarker data were then performed. Neurological symptoms were still present in a significant number ( n = 49) of patients over the follow-up. The most common reported symptoms were hyposmia ( n = 11), fatigue ( n = 28), myalgia ( n = 14), and impaired memory ( n = 11) and were more common in cases with severe acute COVID-19. Follow-up serum NfL values (15.2 pg/mL, range 2.4–62.4) were within normal range in all except 5 patients and did not differentiate patients with vs without persistent neurological symptoms. In patients with available onset and follow-up samples, a significant ( p < 0.001) decrease of NfL levels was observed and was more evident in patients with a severe acute disease. Despite the common persistence of neurological symptoms, COVID-19 survivors do not show active axonal damage, which seems a peculiar feature of acute SARS-CoV-2 infection.